Local strained silicon platform based on differential SiGe/Si epitaxy - Karmous, A.; Oehme, Michael; Werner, J.; Kirfel, O.; Kasper, E.; Schulze, J. (Journal of Crystal Growth, 2011)
Local ultra-thin strained silicon (σSi=1.8GPa) layer on a relaxed SiGe/Si substrate stack has been grown by molecular beam epitaxy in selected spots on the wafer surface defined by patterned windows opened in a SiO2/Si3N4 layer stack. Outside the windows the polycrystalline deposited materials have been removed by chemical mechanical polishing. The strains in the Si and in the SiGe strain relaxed buffer have been investigated using micro-Raman spectroscopy. Based on this growth procedure ultra-thin strained silicon layer on insulator fabrication process is proposed. © 2011 Elsevier B.V.
CRIS-Team Scopus Importer:2021-06-29
Keywords: A1. Strain relaxed buffer; A1. Stresses; A3. Differential MBE; B1. Germanium silicon alloys; B1. Strained silicon; B3. High electron mobility transistors